Rola inicjatywy wspólnotowej LEADER w ekonomiczno-społecznym rozwoju obszarów wiejskich - Jasiulewicz, Anna (The Role of the EU LEADER Initiative in Economic and Social Development of Rural Areas, 2009)
The aim of the article is a presentation of LEADER programme as an example of the support for economic and social development of rural areas. The aim and the content of programme in its following editions and also the aspects connected with realization of this initiative in Poland were presented.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 606-616